2021
DOI: 10.3390/ijms22137165
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome-Wide Isoform Landscape of Melanocytic Nevi and Primary Melanomas Identifies Gene Isoforms Associated with Malignancy

Abstract: Genetic splice variants have become of central interest in recent years, as they play an important role in different cancers. Little is known about splice variants in melanoma. Here, we analyzed a genome-wide transcriptomic dataset of benign melanocytic nevi and primary melanomas (n = 80) for the expression of specific splice variants. Using kallisto, a map for differentially expressed splice variants in melanoma vs. benign melanocytic nevi was generated. Among the top genes with differentially expressed splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…As the collagen-like domain is the site for ligand binding, this may indicate that cancer derived ligands work via MSR1 to help drive the formation of the metastatic form of the disease. On the other hand, the most upregulated isoform in benign nevi was a non-coding transcript with loss of an open reading frame ( 188 ). Further suggesting a role for MSR1 in benign to malignant transformation of tumours.…”
Section: Msr1-positive Tumour Associated Macrophages In Cancermentioning
confidence: 99%
“…As the collagen-like domain is the site for ligand binding, this may indicate that cancer derived ligands work via MSR1 to help drive the formation of the metastatic form of the disease. On the other hand, the most upregulated isoform in benign nevi was a non-coding transcript with loss of an open reading frame ( 188 ). Further suggesting a role for MSR1 in benign to malignant transformation of tumours.…”
Section: Msr1-positive Tumour Associated Macrophages In Cancermentioning
confidence: 99%
“…The pathways which were significantly deregulated only on coding gene expression level had isoform content change in their genes. Particularly, in the cAMP signaling pathway 9 genes (GRIA1, FXYD1, AKT3, NFATC1, NPY1R, PPP1CB, CAMK4, CFTR, PIK3CA) had switched isoforms (e.g., coding isoforms were replaced with noncoding isoforms while the gene expression remained unchanged in groups) which were detected with IsoformSwitchAnalyzeR R package in our previous study ( Hakobyan et al, 2021 ). Another two pathways (AMPK and JAK-STAT signaling) which were also significantly deregulated on coding gene expression analysis also contained isoform switches in 7 genes (TBC1D1, AKT3, RAB2A, CAB39L, PPP2R5E, CFTR, PIK3CA; AKT3, SOCS6, CCND3, IL3RA, IL3RA, PIK3CA, GHR).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, we contemplated that the absence of ycf3 gene introns in H. bogdanii is unusual. Previous research has suggested that a species that a lack of gene introns in a species may indicate that it has taken on additional functions in diverse areas such as protease, RNA polymerase, and ribosomal pathways ( Hakobyan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%